2021
DOI: 10.13048/jkm.21039
|View full text |Cite|
|
Sign up to set email alerts
|

The effectiveness and safety of cupping therapy for stroke survivors: A systematic review and meta-analysis of randomized controlled trials

Abstract: Objectives: ncluding stroke. The aim of this study was to systematically review the clinical evidence of CT for stroke.Methods: To identify randomized controlled trials (RCTs) reporting the effectiveness and/or safety of CT, seven databases including PubMed, EMBASE, and Cochrane Library were searched for articles published from January 2000 to February 2021 without language restrictions. Meta-analysis was performed using Review Manager 5.4 software and the results were presented as mean difference (MD) or stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…This shows that cupping affects the sleep quality of stroke sufferers. 6 Based on research by M. Kim & Han (2021) 19 it was concluded that there was a significant effect with a p-value of 0.001 <0.05 from a randomized controlled trial (RCT). This is in line with the "Theory of Nitric Oxide" and "Reflex Zone Theory" which show that cupping therapy has a relaxing effect on the muscles followed by a calming effect on the patient so that the quality of sleep becomes better.…”
Section: Data Distribution Of Cupping Therapy Pretest and Posttest Re...mentioning
confidence: 99%
“…This shows that cupping affects the sleep quality of stroke sufferers. 6 Based on research by M. Kim & Han (2021) 19 it was concluded that there was a significant effect with a p-value of 0.001 <0.05 from a randomized controlled trial (RCT). This is in line with the "Theory of Nitric Oxide" and "Reflex Zone Theory" which show that cupping therapy has a relaxing effect on the muscles followed by a calming effect on the patient so that the quality of sleep becomes better.…”
Section: Data Distribution Of Cupping Therapy Pretest and Posttest Re...mentioning
confidence: 99%
“…La validación del clasificador bayesiano es un punto crítico a considerar. Se deben llevar a cabo pruebas rigurosas en un conjunto de datos diverso y representativo para evaluar su capacidad para identificar la anemia de manera precisa y confiable(KIM; HAN, 2023). Además, es importante abordar las limitaciones y posibles desafíos en la implementación del sistema, como la variabilidad en las muestras de sangre y la necesidad de un hardware y software especializados.…”
Section: Discusionunclassified
“…La aplicación de redes neuronales convolucionales en el diagnóstico de anemia a partir de imágenes del párpado inferior se basa en la capacidad de estas redes para aprender patrones y características complejas en las imágenes (STARODUBOV et al, 2023) Durante el proceso de entrenamiento, una CNN se expone a una gran cantidad de imágenes etiquetadas de pacientes con y sin anemia. La red ajusta sus pesos y conexiones internas para identificar patrones visuales que son relevantes para la detección de la anemia(KIM; HAN, 2023). Estos patrones pueden incluir variaciones en el color y la textura de la conjuntiva, así como la presencia de vasos sanguíneos dilatados o hemorragias microscópicas.…”
Section: Introduccionunclassified